Analisis Pemahaman Laporan Penelitian Mahasiswa Pendidikan Akuntansi di Universitas Negeri Medan: Penelitian - Helen Natalia Kembaren; Nabilla Putri Andriarsyah; Wasti Maldini Sihombing; Fitriani Lubis (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine students’ understanding in writing research reports, the sections that are best understood and the most difficult ones, as well as their perceptions of the writing process. The research employed a quantitative descriptive method with 23 respondents from the Accounting Education Study Program, Universitas Negeri Medan. The research instruments consisted of a knowledge test with five multiple-choice questions on the structure of research reports and a perception questionnaire with five Likert-scale statements. The findings revealed that students’ understanding was in the good category with an average score of 81.76%. The most understood aspect was the research method (91.3%), while the lowest was the literature review (69.6%). In terms of perception, students showed a positive attitude towards academic format (78.2%) and the ability to distinguish sections of the report (78.2%). However, 26% of respondents experienced difficulties in writing the literature review and 39.1% expressed uncertainty in the discussion section. These results indicate that although students generally understand the structure of research reports, practical writing skills remain a challenge.